ANALISIS TINGKAT EFISIENSI PENGGUNAAN MODAL KERJA DAN PREDIKSI EFISIENSI LANJUTAN PENGGUNAAN MODAL KERJA - ., Subekti (PERMANA, 2011)
This study aims to determine the level of efficient use of working capital and to determine the predictive efficiency of the advanced use of capital in the year 2010-2011.Penelitian uses secondary data consisting of financial statements in 2007 until 2009, consisting of Balance Sheet and Income Statement on persahaan CV. Mitra Jaya Regency Tegal. The research method used there are two analysis are: (1) analysis of the efficient use of working capital consists of the calculation of liquidity ratios to calculate the current ratio and quick ratio, the ratio of the activity and the ratio of profitability. (2) analytical methods Least Squares is to predict the level of efficient use of capital . The results showed that the calculated current ratio during the years 2007 - 2009 is always to increase the smoothness in which the calculation of the ratio above 200%, which falls under the category very well. Quick ratio (quick ratio) is the ability to pay debts that must be filled with more liquid assets. In the quick ratio shows a companys liquidity position either because of close to 100%. From the calculation of turnover of working capital during the years 2007 - 2009 is always decreasing. The ratio of net income before taxes by total assets (Rate of ROA) during the years 2007 to 2009 where the ratio was always decreased profitability in 2007 amounted to 10.29 in 2008 amounting to 8.42 and for 2009 at 8.23. Based on predictions by the method of least squares can be seen that for 2010, predicted current ratio of 599%, 162% fast ratio, 3.51 times the working capital turnover, rate of return on assets 6.40%, 7.20% and profitability. While the prediction for 2011 is the current ratio of 895%, 245% fast ratio, 2.98 times the working capital turnover, rate of return on assets 5.99%, 6.50% and the profitability that shows the state of working capital efficiency. Keywords: Efficiency, Working Capital, the prediction